2021
DOI: 10.30699/ijp.2021.521514.2554
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Studies of 608 couples with Recurrent Spontaneous Abortions in Northeastern Iran

Abstract: Scan to discover onlineBackground & Objective: One of the major genetic causes of recurrent spontaneous abortions is parental chromosomal abnormalities. The objectives of the study were to determine, compare and analyze the incidence and distribution of chromosomal abnormalities in couples with recurrent miscarriages from Northeastern Iran.Methods: This study was conducted at Ghaem Hospital, Mashhad, Iran. We evaluated karyotype results of 608 couples with history of recurrent spontaneous abortion. The standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Many previous studies show that structural chromosomal abnormalities are more common than numerical abnormalities. 15 In our study, we observed 2.2% structural chromosomal aberrations ( Table 2 ). Indeed, in our study, Robertsonian translocations were detected in 1.4% of couples, followed by reciprocal translocations (0.8%).…”
Section: Discussionsupporting
confidence: 55%
“…Many previous studies show that structural chromosomal abnormalities are more common than numerical abnormalities. 15 In our study, we observed 2.2% structural chromosomal aberrations ( Table 2 ). Indeed, in our study, Robertsonian translocations were detected in 1.4% of couples, followed by reciprocal translocations (0.8%).…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, acrocentric chromosomes are susceptible to uniparental disomy (UPD), which occurs with a prevalence of 0.6% in non-homologous RobTs and 66% in homologous RobTs. The data underscores the significant association between recurrent miscarriages and chromosomal structural abnormalities in parents, emphasizing the crucial role of these genetic factors in recurrent pregnancy losses ( 7 ).…”
Section: Introductionmentioning
confidence: 77%
“…Recurrent spontaneous abortion ANRIL decreases (122) Recurrent spontaneous abortion PVT1 decreases (122) Recurrent spontaneous abortion HOTAIR decreases (121) Recurrent spontaneous abortion SNHG5 decreases (119) Recurrent spontaneous abortion H19 increases (113) Recurrent spontaneous abortion MEG8 increases (122) Recurrent spontaneous abortion LINC01088 increases…”
Section: Discussionmentioning
confidence: 99%